2022
DOI: 10.1093/pasj/psac058
|View full text |Cite
|
Sign up to set email alerts
|

Using 3D and 2D analysis for analyzing large-scale asymmetry in galaxy spin directions

Abstract: The nature of galaxy spin is still not fully known. Iye, Yagi, and Fukumoto (2021, AJ, 907, 123) applied a 3D analysis to a dataset of bright SDSS galaxies that was used in the past for photometric analysis. They showed that the distribution of spin directions of spiral galaxies is random, providing a dipole axis with low statistical significance of 0.29σ. However, to show random distribution, two decisions were made, each of which can lead to random distribution regardless of the real distribution of the spin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 194 publications
1
35
0
Order By: Relevance
“…Analysis with a higher number of more than 6•10 3 galaxies from the southern hemisphere showed that the distribution is random [13]. As explained in [17], given the expected magnitude of the parity violation, the number of galaxies used in that study was too small to show a statistically signifcant parity violation. On the other hand, analysis of a larger number of galaxies from SDSS showed evidence of parity violation that forms a statistically signifcant dipole axis [1,69].…”
Section: Summary Of Previous Work On Asymmetry In the Spin Direction ...mentioning
confidence: 74%
See 4 more Smart Citations
“…Analysis with a higher number of more than 6•10 3 galaxies from the southern hemisphere showed that the distribution is random [13]. As explained in [17], given the expected magnitude of the parity violation, the number of galaxies used in that study was too small to show a statistically signifcant parity violation. On the other hand, analysis of a larger number of galaxies from SDSS showed evidence of parity violation that forms a statistically signifcant dipole axis [1,69].…”
Section: Summary Of Previous Work On Asymmetry In the Spin Direction ...mentioning
confidence: 74%
“…Tat study, however, does not refer to a specifc paper that claimed for the presence of a dipole axis formed by the distribution of galaxy spin directions and also had duplicate objects in the data. Also, a simple analysis showed that the "clean" data used in [16] is in fact not random [17]. Code and data to reproduce the analysis are available at https://people.cs.ksu.edu/~lshamir/ data/iye_et_al.…”
Section: Summary Of Previous Work On Asymmetry In the Spin Direction ...mentioning
confidence: 99%
See 3 more Smart Citations